Evaluation of the Implementation of the Fixed Asset Accounting Security Procedure System in the Regional Government of Bogor Regency - Dea Witriyani (The Graduate School of Sahid University, 2023)
The Bogor Regency regional government must present detailed financial reports describing asset values, regulated in Government Accounting Standard Regulation No. 7 of 2010. On the other hand, the problem in regional asset management is the lack of orderly administration and legal order which has resulted in regional assets, especially regional fixed assets, not being able to be properly and accurately inventoried, the lack of previous technology, which is still limited makes some of the data owned by the Government Regions are not valid, coupled with Human Resources (HR) which are still very limited. The research aims to examine the implementation of the Fixed Assets Accounting Systems and Procedures and the safeguarding of fixed assets that the Government of Bogor Regency has implemented. The research method used is descriptive qualitative, which is a method that describes the problems or cases raised based on existing facts based on specific facts and then examines them to solve problems and draw general conclusions. The Bogor Regency Government 2013 launched the Regional Goods Cycle Information Technology Application (ATISISBADA), which implements Fixed Assets Accounting Systems and Procedures and safeguards fixed assets. The technology-based fixed asset information system assists administration or online administrative/inventory recording that coordinates the Management of Regional Property in Bogor Regency, which has 40 Districts and 38 SKPDs or Regional Apparatuses with a large number of assets in the Bogor Regency Government with a considerable value. The conclusion of the research on securing regional property on fixed assets in Bogor Regency is good regarding procedures or implementation of regional property management, especially on physical, administrative, and legal security.